Joint angular positions that influence volleyball attack height in men's players - Hsieh, C. T. (ISBS Proceedings Archive (Michigan), 2019)
The aim of this study was to identify the angular position differences between high (HP) and low (LP) men`s volleyball performers at the instant of take-off and ball impact. Ten skilled collegiate men`s volleyball players were recruited from the university club team. All joint angular positions were obtained via 3D motion analysis. Results indicated that the HP players had greater normalized CoM (p < 0.004) and reach height (p < 0.004) at the instant of take-off and ball impact than the LP players, respectively. At the instant of take-off, HP players had a greater extension at hips, right knee, right elbow, left shoulder (flexion), and right shoulder (abduction) than LP players (p < 0.004). At the instant of ball impact, the HP players demonstrated greater right elbow extension, right ankle plantar flexion, right shoulder abduction, and smaller left shoulder flexion than the LP players (p < 0.004).